2019
DOI: 10.1155/2019/2629464
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Gold Nanoparticles via Galvanic Replacement in DMSO and Their Influence on Formation of Silicon Nanostructures

Abstract: The process of gold nanoparticle (AuNP) precipitation on the silicon (Si) surface by galvanic replacement (GR) in dimethyl sulfoxide (DMSO) solution depending on the concentration of H[AuCl4], temperature, and duration was investigated. It is established that with an increase in the concentration of [AuCl4]− ions (from 2 to 8 mM H[AuCl4]), both the size of AuNPs and their surface coverage density are increased. It is demonstrated that an increase in temperature causes the size of AuNPs to increase from 40 to 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…AuNPs and AuNSs are accentuated among the existing NSs for various applications and there are various methods such as atomic layer deposition, laser ablation, sputtering, and so forth, that exist in the literature for preparing them ( Byram et al., 2019 ; Hatakeyama et al., 2011 ; Hashemi et al., 2020 ; Palazzo et al., 2017 ). By counting on the cost-effectiveness and ease of handling, the preparation of AuNPs favors a facile galvanic displacement (GD) process, which results in the homogeneous distribution of NPs over the aimed surface ( Gutes et al., 2011 ; Srikanth and Jeevanandam, 2012 ; Shepida et al., 2019 ; Magagnin et al., 2002 ; Zhang et al., 2015 ). The existing findings in the literature on Au and AgNSs motivated us to fabricate bimetallic Au/Ag nanostructures by combining a facile electroless and galvanic deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs and AuNSs are accentuated among the existing NSs for various applications and there are various methods such as atomic layer deposition, laser ablation, sputtering, and so forth, that exist in the literature for preparing them ( Byram et al., 2019 ; Hatakeyama et al., 2011 ; Hashemi et al., 2020 ; Palazzo et al., 2017 ). By counting on the cost-effectiveness and ease of handling, the preparation of AuNPs favors a facile galvanic displacement (GD) process, which results in the homogeneous distribution of NPs over the aimed surface ( Gutes et al., 2011 ; Srikanth and Jeevanandam, 2012 ; Shepida et al., 2019 ; Magagnin et al., 2002 ; Zhang et al., 2015 ). The existing findings in the literature on Au and AgNSs motivated us to fabricate bimetallic Au/Ag nanostructures by combining a facile electroless and galvanic deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the distribution of Au nanoparticles in height remains low for all concentrations of the reducible metal. The process of galvanic replacement of gold can be described by the following redox reactions [17]:…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work we demonstrated that an increase in temperature of solution containing [AuCl 4 ]ions and its concentration causes the size enlargement of AuNPs [17]. However, the effect of the morphology of Au sediment deposited onto Si substrate in a DMSO solvent by galvanic replacement method on the formation of Si nanostructures by means of MACE method was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ways to modify conventional semiconductor materials have been actively studied. These include galvanic replacement [1][2][3], doping with various impurities [4][5][6], substitution of elements in the form of solid solutions [7][8], etc. The listed methods allow to adjust the properties of semiconductors for their more efficient use in electronic applications and devices.…”
Section: Introductionmentioning
confidence: 99%